2012
DOI: 10.1016/j.jchromb.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of multiple phthalate metabolites and bisphenol-A in human urine by liquid chromatography–tandem mass spectrometry

Abstract: Phthalates and bisphenol A are environmental endocrine-disrupting chemicals used widely in common consumer products. There is increasing concern about human exposure to phthalates and bisphenol A due to the potential adverse effects related to the anti-androgenic activity of phthalates and estrogenic activity of bisphenol A. In assessing environmental exposure to phthalates and bisphenol A, it is essential to have a validated analytical method that can quantify trace concentrations of phthalate metabolites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…The efficiency of the presented DLLME method for BPA was compared with other sample preparation techniques such as molecularly imprinted solid phase extraction [34], solid phase extraction [35], molecularly imprinted solid phase microextraction [36], in-tube solid phase microextraction [37], liquid phase microextraction gas chromatography mass spectrometry [38], hollow fiber assisted liquid-phase microextraction gas chromatography mass spectrometry [39] and solid phase extraction liquid chromatography mass spectrometry [40] from the viewpoint of linearity, LOD, RSD and preconcentration factor which are shown in Table 1. It can be observed that the analytical performance of the present method is comparable with other reported extraction methods except methods coupled with mass detector.…”
Section: Analytical Performance Of the Methods And Its Comparison Withmentioning
confidence: 99%
“…The efficiency of the presented DLLME method for BPA was compared with other sample preparation techniques such as molecularly imprinted solid phase extraction [34], solid phase extraction [35], molecularly imprinted solid phase microextraction [36], in-tube solid phase microextraction [37], liquid phase microextraction gas chromatography mass spectrometry [38], hollow fiber assisted liquid-phase microextraction gas chromatography mass spectrometry [39] and solid phase extraction liquid chromatography mass spectrometry [40] from the viewpoint of linearity, LOD, RSD and preconcentration factor which are shown in Table 1. It can be observed that the analytical performance of the present method is comparable with other reported extraction methods except methods coupled with mass detector.…”
Section: Analytical Performance Of the Methods And Its Comparison Withmentioning
confidence: 99%
“…The categories of reported use are consistent with a prior evaluation of exposures among custodians using the interval of more or less than 4 h to describe exposure intensity (Obadia et al, 2009). The four different phthalate monoester metabolites (MEP, MMP, MEHP, and MBzP) were quantified in the urine using liquid chromatography-tandem mass spectrometry (LC-MS/MS) according to the analytical and quality control methods previously described (Chen et al, 2012). The limit of quantitation (LOQ) for each phthalate metabolite was: MEP (0.5 ng ml ).…”
Section: Urine Sample Collectionmentioning
confidence: 96%
“…Internal standard (IS) of D 16 -BPA was prepared in acetonitrile at a concentration of 1000 mg/L, and then diluted to 2.0 mg/L with acetonitrile as working standard solutions. All stock solutions were stored at 4ЊC in the refrigerator.…”
Section: Preparation Of Standardsmentioning
confidence: 99%
“…Working standard solutions were prepared by mixing 5, 25, 50, 100, and 250 L of mixed working standard (0.2 mg/L), with 25 L internal standard (D 16 -BPA, 2.0 mg/L). The working standard solutions were dried by N 2 flow at 50ЊC, and then derived and analyzed by GC-MS.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation